A genetic assessment of the taxonomic status of New Zealand mussels of the genus Xenostrobus Wilson, 1967. Issue 2 (2nd April 2020) - Colgan, Donald J.; Willan, Richard C.; Kirkendale, Lisa A.
ABSTRACT: The genus Xenostrobus consists of small, marine and estuarine mussels that all appear similar externally. One of its estuarine species, Xenostrobus securis, with a native range in New Zealand and Australia, has become invasive in the Northern Hemisphere. No genetic data are available to determine if X. securis populations from the two countries are conspecific. Additionally, marine Xenostrobus from New Zealand have often been regarded as a species, X. neozelanicus, distinct fromthe marine Australian species X. pulex . We combined new DNA sequences with published data to assess the taxonomic status of New Zealand Xenostrobus. The data comprised 658 aligned bases of mitochondrial cytochrome c oxidase subunit I (COI) gene and 331 bases of nuclear histone H3. There was no evidence that X. securis populations from Australia and New Zealand are specifically distinct. Northern Hemisphere specimens of X. securis belonged to Australian, not New Zealand, clades in phylogenetic analyses of COI data, suggesting the former country as their more likely original source. The results confirm that X. neozelanicus and X. pulex are distinct species and for nomenclatural completeness for this taxonomic decision a lectotype is designated for Mytilus ater Zelebor in Dunker and Zelebor, 1866 [ =  Modiolus neozelanicus Iredale, 1915 ].